2014
DOI: 10.1186/s13717-014-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of urban soils: the case of the Beijing metropolitan region, China

Abstract: Introduction: Urban soils are large pools of carbon, nitrogen, and other elements, supporting plant growth, sustaining biogeochemical cycles, and serving as the foundation for maintaining ecosystem function and services of urban green spaces (UGS). Quantifying urban soil properties is essential for assessing urban ecosystem services and detecting pollution. Characterizing spatial heterogeneity of urban soil properties, which may change with land use or urbanization, is crucial for understanding urban ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
(66 reference statements)
2
24
1
Order By: Relevance
“…Soils from transport routes or roadsides and residential areas have high concentrations of heavy metals because they were frequently disturbed by human activities. This finding was consistent with similar earlier studies 5,11. Another factor that may increase concentrations of the heavy metals is the low pH of some of the surface soils.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Soils from transport routes or roadsides and residential areas have high concentrations of heavy metals because they were frequently disturbed by human activities. This finding was consistent with similar earlier studies 5,11. Another factor that may increase concentrations of the heavy metals is the low pH of some of the surface soils.…”
Section: Discussionsupporting
confidence: 93%
“…The maximum mean concentration of Cu in this study was higher than the 28.82 mgkg −1 and 31.63 mgkg −1 measured in industrial and roadside soils in Beijing metropolitan region, China 11. The mean Cu concentration for urban soils in Ijebu-ode (14.71 mgkg −1 ) was, however, lower than the 30.17 mgkg −1 level recorded for residential areas in Beijing 11. Copper is a metal with very low mobility and studies have shown that it tends to accumulate in topsoil 3,43.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Gradients in soil properties have been studied at the scales of patches (Jenerette et al 2010), cities (Pouyat et al 2006;Pouyat et al 2010), regions (Pouyat et al 2007;Li et al 2013), and globally (Pouyat et al 2006). The urban-rural gradient paradigm characterizes variation in soils with respect to the degree of urbanization as measured by land-use intensity (Su et al 2019), style of land management (Mao et al 2014), particular microenvironments (Liu et al 2007), and/or the ora and fauna that compose soils (Zhu and Carreiro 1999;Zhao et al 2010). This paradigm is considered useful for describing effects of urbanization on soil nutrients due to its simplicity and effectiveness (Bennett 2003;Vasenev et al 2013;Chen et al 2014;Meng et al 2018).…”
Section: Introductionmentioning
confidence: 99%